Outcomes and Prognostic Factors of Intravitreal Bevacizumab Monotherapy in Zone I Stage 3+ and Aggressive Posterior Retinopathy of Prematurity - Simona Delia Nicoară; Constanța Nascutzy; Cristina Cristian; Iulian Irimescu; Anne Claudia Ștefănuț; Gabriela Zaharie; Tudor Drugan (Journal of Ophthalmology)
Purpose. This study aims to evaluate the regression of retinopathy of prematurity (ROP) after one intravitreal injection of bevacizumab and the factors that influenced it. Methods. This retrospective case series was carried out at the “Iuliu Hațieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania. It includes all the consecutive infants treated for ROP with one intravitreal bevacizumab injection, from January 1, 2009, throughout July 31, 2013. The follow-up continued for 60 weeks after injection. We recorded ROP classification, regression, gender, gestational age, birth weight, postnatal age and postmenstrual age at treatment, and pregnancy type. Regression was analyzed according to each of the abovementioned factors, with the program IBM SPSS 20 (Chicago, Illinois, USA). Results. This study includes 74 eyes of 37 infants of which 52 had aggressive posterior ROP (70.27%) and 22 had zone I stage 3+ ROP (29.72%). One week after the bevacizumab injection, ROP regressed in 63 eyes (85.13%), with a statistically significant higher rate in zone I stage 3+ ROP (100%), as compared with aggressive posterior ROP (78.84%) (P=0.03). We recorded no complications subsequent to the intravitreal injections of bevacizumab. We identified no late retinal detachment. Conclusion. ROP regression rate after one intravitreal bevacizumab injection was 85.13%. This trial is registered with trial registration number IRCT2014101618966N2.